Hybridization of Palladium Nanoparticles with Aromatic‐Rich SU‐101 Metal‐Organic Framework for Effective Transfer Hydrogenation. Issue 25 (13th July 2022) - Krishnaveni, Valle; Esclance DMello, Marilyn; Basavaiah, Keloth; Samsonu, Dasi; Rambhia, Dheer A.; Kalidindi, Suresh Babu
Abstract: Metal‐organic frameworks (MOFs) are crystalline porous materials with designable pores. In this study, we loaded Pd nanoparticles onto π‐electron rich pores of ellagic acid based SU‐101 MOF (Bi2 O(H2 O)2 (C14 H2 O8 ) ⋅ nH2 O) in order to surround Pd active sites with π‐electron rich environment. The material has been explored for the transformation of 4‐Nitro phenol (4‐NP) to 4‐Amino phenol (4‐AP) using ammonia borane (AB). AB acted as efficient transfer hydrogenation agent compared to NaBH4 because of its ability to transfer hydrogens at milder conditions. AB is safer and easy to handle compared to molecular hydrogen or NaBH4 . The Pd NPs are loaded on to SU‐101 using two methodologies. One by supporting preformed Pd NPs onto MOF surface (Pd‐WCGA/SU‐101) and the other by wet impregnation method (Pd/SU‐101). The later method yields a material with strong interaction between Pd and SU‐101. The Pd/SU‐101 exhibited superior activity for 4‐NP reduction (turn over frequency=2421 h −1 ) using AB due to an enrichment of 4‐NP around Pd active sites by π‐electron rich pore environment. Abstract : Hybridization of Pd with π‐electron rich SU‐101 MOF lead to the development of effective catalyst for 4‐nitrophenol reduction using ammonia borane. Wet impregnation method led to the formation of smaller Pd nanoparticles and full 4‐NP conversion has been realized in 10 min with TOF of 2, 421 h −1 .